1994
DOI: 10.1093/jxb/45.special_issue.1743
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation that abscisic acid accumulation is required for maize primary root elongation at low water potentials

Abstract: Previous work showed that primary root elongation in maize (Zeamays L.) seedlings at low water potentials was severely inhibited when accumulation of abscisic acid (ABA) was decreased using either fluridone or the vp5 mutant to inhibit carotenoid (and ABA) biosynthesis. The objective of this study was to confirm that the inhibition of root elongation resulting from these treatments was indeed attributable to the decrease in ABA levels. Seedlings were transplanted after germination to vermiculite at water poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(118 citation statements)
references
References 18 publications
9
103
0
4
Order By: Relevance
“…The ABA was shown to inhibit shoot growth more than root growth (Saab et al 1990). Sharp et al (1994) also found a requirement of high ABA accumulation for maintenance of root elongation under low soil water potential. However, recent study showed that ABA has been found to inhibit the secondary root development as an adaptive response to the drought stress (Xiong et al 2006).…”
Section: Introductionmentioning
confidence: 89%
“…The ABA was shown to inhibit shoot growth more than root growth (Saab et al 1990). Sharp et al (1994) also found a requirement of high ABA accumulation for maintenance of root elongation under low soil water potential. However, recent study showed that ABA has been found to inhibit the secondary root development as an adaptive response to the drought stress (Xiong et al 2006).…”
Section: Introductionmentioning
confidence: 89%
“…Increasing evidence indicates that this is not necessarily the case. Decreases in plant water status have been shown to change the compartmentation (Hartung, Radin & Hendrix 1988;Bacon, Wilkinson & Davies 1998), apparent sensitivity (Tardieu & Davies 1992;Dodd & Davies 1996) and response (Sharp et al . 1994) to ABA in various organs.…”
Section: Approaches To Study the Role Of Aba In Growth Responses To Wmentioning
confidence: 99%
“…Initial studies used the fluridone and vp5 mutant approaches (Saab et al . 1990;Saab, Sharp & Pritchard 1992;Sharp et al . 1994).…”
Section: Aba Accumulation Maintains Maize Primary Root Growth At Low mentioning
confidence: 99%
“…However, the involvement of other signals and how these other signals interact with the ABA signal remain unanswered questions. These questions arise, at least in part, from a number of observations that have shown that ABA applied to unstressed plants often does not elicit the same response as ABA accumulation that occurs under stress conditions (Sharp et al 1994;Imai et al 1995;Verslues and Bray 2006). Control of ABA accumulation and sensitivity also appears to involve extensive feedback regulation (Xiong et al 2002;Verslues and Bray 2006).…”
Section: Introductionmentioning
confidence: 99%